Comprehensive Comparison of VNE Solutions Based on Different Coordination Approaches - Stelios Prekas; Panagiotis Karkazis; Vasileios Nikolakakis; Panagiotis Trakadas (Telecom, 2021)
Virtualization is commonly accepted as the catalyst that would grant the internet the ability to shed the shackles of legacy technologies and evolve to its future self. In order to make this transformation feasible, unavoidable concurrent radical remodeling of all the involved counterparts is required, particularly in the context of automatically and optimally serving application requests by taking advantage of new virtualized environments and their latent capabilities. A considerable number of embedding strategies that efficiently map virtual computational and networking demands over physical resources have already been proposed in the literature, following different strategies. Among these suggested strategies, different coordination proposals have been adopted, in order to solve the node and link mapping functions. In this paper, we study the capabilities of the most popular embedding strategies, based on their coordination categorization. Our study confirms that by invoking a coordination strategy, especially the single stage one, added benefits on multiple performance layers can be achieved. Moreover, we propose a new mixed coordination algorithm, essentially creating a new category in the field of VNE coordination strategies.